2019
DOI: 10.1093/jas/skz272
|View full text |Cite
|
Sign up to set email alerts
|

Supplementing calcium salts of soybean oil to beef steers early in life to enhance carcass development and quality1

Abstract: This study evaluated the effects of supplementing Ca salts of soybean oil (CSSO) to beef steers at 2 mo of age via creep-feeding, and/or during a 40-d preconditioning period on performance and carcass development responses. A total of 64 steers were enrolled in this study over 2 yr (32 steers per year), with 4 periods each year: creep-feeding (CF; day 0 to 60), preweaning (day 61 to weaning on day 124 and 127 of year 1 and 2, respectively), preconditioning (PC; day 132 to 172 in year 1 and day 135 to 175 of ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 53 publications
1
18
2
Order By: Relevance
“…Moreover, CSVO supplementation also reduced the mRNA expression of SCD vs. CONT cohorts. These results do not agree with Schubach et al (2019) in which effects were either positive or similar between CSSO- and SFA-supplemented cohorts. Additionally, the reason why the results herein were different is intriguing, given that in agreement to PPAR-γ effects on lipid metabolism, enhanced SREBP-1 expression indicates a greater capacity of de novo FA synthesis and lipid accumulation in muscle tissue ( Zhao et al, 2010 ).…”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…Moreover, CSVO supplementation also reduced the mRNA expression of SCD vs. CONT cohorts. These results do not agree with Schubach et al (2019) in which effects were either positive or similar between CSSO- and SFA-supplemented cohorts. Additionally, the reason why the results herein were different is intriguing, given that in agreement to PPAR-γ effects on lipid metabolism, enhanced SREBP-1 expression indicates a greater capacity of de novo FA synthesis and lipid accumulation in muscle tissue ( Zhao et al, 2010 ).…”
Section: Discussioncontrasting
confidence: 85%
“…In agreement with our results, Fiorentini et al (2014) also observed similar ADG, FE, and carcass characteristics of beef animals receiving a 60:40 roughage:concentrate diet containing calcium salts of soybean oil or whole soybeans. Moreover, Schubach et al (2019) also reported similar performance and carcass characteristics when different sources of calcium salts of fatty acids (palm- and soybean oil-based) were strategically supplied to cattle on creep-feeding (60 d) and/or preconditioning (40 d). Conversely, Nascimento (2017) reported greater HCW, BFT, and REA of B. indicus beef animals offered CSVO vs. CSSO during feedlot for a period of 140 d. Cooke et al (2011) also reported greater marbling in animals supplemented with a source of calcium salts of soybean oil for 28 d during preconditioning prior to transport to feedlot.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…As previously noted, LMB intake during the initial 14 d were beyond the expected and nearly double the supplement intake of CONC cows, explaining differences observed between these treatments in samples collected on day 14. The decrease in plasma α-linolenic acid and ɷ-3 polyunsaturated FA concentrations in CSSO-supplemented cattle has also been reported by our group in research with mature and growing beef cattle ( Cooke et al, 2011 ; Brandão et al, 2018 ; Schubach et al, 2019 ). On days 28 and 42, when CONC intake was adjusted to match LMB intake ( Table 3 ), plasma concentrations of palmitic acid, stearic acid, linoleic acid, γ-linolenic acid, dihomo-γ-linolenic acid, osbond acid, total saturated FA, total polyunsaturated FA, total ω-6 polyunsaturated FA, and total FA were greater in CONC and LMB vs. NOSUPP cows and did not differ ( P ≥ 0.35) between LMB and CONC cows.…”
Section: Resultssupporting
confidence: 80%
“…The mechanisms underlying the outcomes reported by Marques et al (2017) still warrant investigation, including the individual role of ɷ-3 and ɷ-6 FA. In recent studies with beef cattle, linoleic acid and its ɷ-6 derivatives were the specific FA linked with fetal cell differentiation and development ( Schubach et al, 2019 ). Hence, supplementing a FA source based on ɷ-6 such as Ca salts of soybean oil (CSSO), may be more advantageous to gestational programming compared with the ɷ-3 + ɷ-6 FA mix used by Marques et al (2017) , and also elucidate the specific programming roles of ɷ-6 FA.…”
Section: Introductionmentioning
confidence: 99%